Perspectives and recommendations towards evidence-based health care for scorpion sting envenoming in the Brazilian Amazon: A comprehensive review. (November 2019) - Monteiro, Wuelton Marcelo; Gomes, Jacimara; Fé, Nelson; Mendonça da Silva, Iran; Lacerda, Marcus; Alencar, Aristóteles; Seabra de Farias, Altair; Val, Fernando; de Souza Sampaio, Vanderson; Cardoso de Melo, Gisely; Pardal, Pedro; Mota da Silva, Ageane; et al.
Abstract: Although underreported across the Amazon region, scorpion stings are very prevalent in some areas and can be potentially life-threatening, especially in children. The most vulnerable populations are those living in locations far from the capitals, hence having limited access to the health system where the appropriate structure for the treatment of severe cases is found. An abundant and diverse fauna of scorpions is found in the region, but few studies have been conducted to decipher the clinical characteristics and therapeutic response of the available antivenoms in envenomings caused by the various species. Antivenom underdosage as well as delayed medical assistance are common among indigenous populations, resulting in poor outcome rates. An in depth understanding of the epidemiological, clinical and therapeutic aspects of scorpion sting envenomings in the Amazon is necessary to improve the outcome of these cases. Highlights: Scorpion stings are a great burden in the amazon region with riverine and indigenous becoming the most affected populations. Scorpions from the Tityus genus have been associated to clinically mild and severe human accidents, mainly in children. Local and systemic manifestations have been reported. However, a classification system for the amazon region is absent. Studies addressing venom composition and associated pathophysiology of the Amazonian scorpion fauna are scarce. Available antivenoms are not adequate and medical training and assistance in the region is insufficient.